Exopolysaccharides favor the survival of Erwinia amylovora under copper stress through different strategies - Ordax, Mónica; Marco-Noales, Ester; López, María M.; Biosca, Elena G. (2017)
Erwinia amylovora causes fire blight, a destructive disease of rosaceous plants very difficult to control. We demonstrated that copper, employed to control plant diseases, induces the "viable-but-nonculturable" (VBNC) state in E. amylovora. Moreover, it was previously reported that copper increases production of its main exopolysaccharide (EPS), amylovoran. In this work, the copper-complexing ability of amylovoran and levan, other major EPS of E. amylovora, was demonstrated. Following this, EPS-deficient mutants were used to determine the role of these EPSs in survival of this bacterium in AB mineral medium with copper, compared to their wild type strain and AB without copper. Total, viable and culturable counts of all strains were monitored for six months. With copper, a larger fraction of the viable population of EPS mutants entered into the VBNC state, and earlier than their wild type strain, showing the contribution of both EPSs to long-term survival in a culturable state. Further, we demonstrated that both EPSs can be used as carbon source by E. amylovora under deprivation conditions. Overall, these previously unreported functions of amylovoran and levan provide survival advantages for E. amylovora, which could contribute to its enhanced persistence in nature. (C) 2010 Elsevier Masson SAS. All rights reserved.